Unconventional Approaches to Hydrogen Sorption Reactions: Non‐Thermal and Non‐Straightforward Thermally Driven Methods. Issue 10 (7th March 2019) - Ares, Jose‐Ramón; Nevshupa, Roman; Muñoz‐Cortés, Esmeralda; Sánchez, Carlos; Leardini, Fabrice; Ferrer, Isabel‐J.; Minh Huy Tran, Vo; Aguey‐Zinsou, Francois; Fernández, Jose‐Francisco
Abstract: In the last decades, a broad family of hydrides have attracted attention as prospective hydrogen storage materials of very high gravimetric and volumetric capacity, fast H2 ‐sorption kinetics, environmental friendliness and economical affordability. However, constraints due to their high activation energies of the different H2 ‐sorption steps and the Gibbs energy of their reaction with H2 has led to the need of high thermal energy to drive H2 uptake and release. High heat leads to significant degradation effects (recrystallization, phase segregation, nanoparticles agglomeration…) of the hydrides. In this context, this short review aims to summarize alternative non‐thermal methods and non‐straightforward thermally driven methods to overcome the previous constraints. The phenomenology lying behind these methods, i. e. tribological activation, sonication, and electromagnetic radiation, and the effect of these processes on hydrogen sorption properties of hydrides are described. These non‐usual approaches could boost the capability of the next generation of solid‐hydride materials for hydrogen conversion in energy sector, in mobile devices and as hydrogen reservoirs. Abstract : Unconventional approaches ? The influence of rather uncommon energy sources (illustrated in the picture) on H2 ‐sorption properties of hydrides are described and analyzed in this minireview.